Identifying Stakeholder Groups in Natural Resource Management: Comparing Quantitative and Qualitative Social Network Approaches. Issue 7 (2nd July 2020) - Wutich, Amber; Beresford, Melissa; Bausch, Julia C.; Eaton, Weston; Brasier, Kathryn J.; Williams, Clinton F.; Porter, Sarah
Abstract: This study compares the efficiency of two analytic approaches—qualitative and quantitative—to social network analysis for identifying stakeholder groups. Social network data were collected from 23 water and agriculture stakeholders in Arizona, USA, and analyzed quantitatively and qualitatively. Analysis of the sample in the original order of data collection found qualitative analysis was more efficient, in that it yielded a stable result—the identification of four stakeholder groups—within 16 interviews. In contrast, the quantitative analysis did not produce a stable result after 23 interviews. Repeated analyses with randomized order and reverse order samples found qualitative approaches yielded more stable results, took about the same number of interviews to yield results, and produced slightly fewer stakeholder groups compared to quantitative approaches. Our findings suggest that, in resource-constrained projects, qualitative social network analysis for identifying stakeholder groups can provide an efficient alternative to conventional quantitative social network analysis.